2017
DOI: 10.1371/journal.pone.0178665
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential changes in liver and lung tissue of rats in an ischemia-reperfusion injury model (modified pringle maneuver)

Abstract: In surgical procedures involving the liver, such as transplantation, resection, and trauma, a temporary occlusion of hepatic vessels may be required. This study was designed to analyze the lesions promoted by ischemia and reperfusion injury of the hepatic pedicle, in the liver and lung, using histopathological and immunohistochemical techniques. In total, 39 Wistar rats were divided into four groups: control group (C n = 3) and ischemia groups subjected to 10, 20, and 30 minutes of hepatic pedicle clamping (I1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 25 publications
(19 reference statements)
2
20
0
9
Order By: Relevance
“…There are experimental studies described in literature for comprehension of the pathophysiology and the establishment of therapies for ischemia and reperfusion injuries (Yassin et al 1997, Camargo et al 2003, Chang et al 2005, Ribeiro & Yoshida 2005, Gonzalez et al 2015, Freitas et al 2017. However, when the pilot study of the present project was initiated, we found a discrepancy in results obtained from those described by authors using a similar methodology to the one employed.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…There are experimental studies described in literature for comprehension of the pathophysiology and the establishment of therapies for ischemia and reperfusion injuries (Yassin et al 1997, Camargo et al 2003, Chang et al 2005, Ribeiro & Yoshida 2005, Gonzalez et al 2015, Freitas et al 2017. However, when the pilot study of the present project was initiated, we found a discrepancy in results obtained from those described by authors using a similar methodology to the one employed.…”
Section: Discussionmentioning
confidence: 68%
“…Among the described experimental models, there are studies performed on rats, rabbits, dogs, cats, pigs and horses (Camargo et al 2003, Kostopanagiotou et al 2007, Avgerinos et al 2010, Yurdakan et al 2012, Freitas et al 2017). According to Ribeiro & Yoshida (2005), the most experimentally used test subjects are rodents, represented by about 73% of the studies, mainly for their ease to work with, adequateness to protocols, availability and low cost, as well as their anatomy being similar to humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initiator caspases induce and trigger the apoptotic cascade, while effector caspases carry out the cell death program. Caspase‐3 is generally known as a major effector caspase . Malondialdehyde (MDA) is an end‐product of lipid peroxidation, representing a well‐known example of oxidative damage in cell membranes brought about by ROS in the ischemia‐reperfusion period…”
Section: Introductionmentioning
confidence: 99%
“…However, the maintenance of oxidative stress differs between both types of ischemia. Concerning to metabolism and molecular pathways, warm ischemia is more damaging, because, in hypothermic ischemia, cellular metabolism and ATP consumption are significantly lower [1][2]4 .It is apparently paradoxical that in steatotic livers, the I/R lesion tends to be even worse, depending on the degree of steatosis; the worst results are obtained in the moderate and severe cases of microvesicular steatosis. Thus, in steatosis, worsening of graft and receptor survival is observed in the case of transplants, with the increased histological lesion and hepatic functional derangement 5-6 .The pathophysiology of liver ischemia and reperfusion injury are always evolutionary justifying, as clear rationale, the constant update to discuss new horizons in preconditioning and therapy.…”
mentioning
confidence: 99%